Enhanced thermoelectric performance through crystal field engineering in transition metal–doped GeTe. (June 2019) - Shuai, J.; Tan, X.J.; Guo, Q.; Xu, J.T.; Gellé, A.; Gautier, R.; Halet, J.-F.; Failamani, F.; Jiang, J.; Mori, T.
Abstract: The change of multivalence band structure configuration between rhombohedral and cubic phase in GeTe offers additional dimension to modify its thermoelectric properties. Here, we report the synergetic optimization of electronic and thermal transport properties in rhombohedral GeTe doped with transition metal Ti. The Seebeck coefficient of Ge1-x Tix Te is significantly increased, and the corresponding thermal conductivity is decreased. The structure refinement shows that Ti doping could reduce the lattice constant c / a ratio. Density functional theory calculations demonstrate that the affected crystal field rather than Ti orbitals is contributing to the valence band convergence and a Seebeck coefficient enhancement. Further optimization incorporates the effects of Bi substitution for reducing the carrier concentrations and introducing more point defects. This work not only confirms the transition metal elements as promising dopants for GeTe-based materials but also indicates that the strategy of manipulating the crystal field effect can be exploited as a direct but effective route for improving thermoelectric performance. Graphical abstract: Image 1 Highlights: Enhanced Seebeck coefficient and decreased thermal conductivity upon Ti doping. Further optimized by decreasing carrier concentration and lattice thermal conductivity with co-doping Bi and Ti at Ge sites. Proof of manipulation of crystal field effect as a feasible route of band engineering for thermoelectric enhancement of GeTe.